2008
DOI: 10.3748/wjg.14.6145
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl sulfide protects against N -nitrosodiethylamineinduced liver tumorigenesis: Role of aldose reductase

Abstract: AIM:To evaluate the protective effect of diallyl sulfide (DAS) against N -nitrosodiethylamine (NDEA)-induced liver carcinogenesis. METHODS: Male Wistar rats received either NDEA or NDEA together with DAS as protection. Liver energy metabolism was assessed in terms of lactate, pyruvate, lactate/pyruvate, ATP levels, lactate dehydrogenase (LDH) and glucose-6-phosphate dehydrogenase (G6PD) activities. In addition, membrane disintegration of the liver cells was evaluated by measuring lipid-peroxidation products, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 55 publications
2
20
0
2
Order By: Relevance
“…Scuric et al [83] found a significantly increased AR mRNA levels in the livers of hepatocellular cancer patients compared to normal liver. Together, these observations strongly suggest that AR is overexpressed during oxidative stress– induced hepatocarcinogenesis [86]. In this context, various reports show the use of antioxidants against inflammation/ROS -induced hepatocarcinogeneis.…”
Section: Role Of Ar In Carcinogenesismentioning
confidence: 97%
“…Scuric et al [83] found a significantly increased AR mRNA levels in the livers of hepatocellular cancer patients compared to normal liver. Together, these observations strongly suggest that AR is overexpressed during oxidative stress– induced hepatocarcinogenesis [86]. In this context, various reports show the use of antioxidants against inflammation/ROS -induced hepatocarcinogeneis.…”
Section: Role Of Ar In Carcinogenesismentioning
confidence: 97%
“…3B). For instance, protective effects of DAS treatment were observed in N-nitrosodiethylamine (NDEA)-induced liver tumorigenesis [36]. While NDEA treatment compromised several indices of liver function, DAS treatment normalized all non-enzymatic and enzymatic liver functions affected by NDEA.…”
Section: Protective Effects Of Dasmentioning
confidence: 99%
“…Thus, a decreased A/G ratio often indicates the presence of impaired liver function (Ibrahim et al, 2008). DENA significantly decreased total protein, albumin, and A/G levels, which indicated poor liver function and inability to fight infections.…”
Section: Discussionmentioning
confidence: 99%